2020
DOI: 10.20452/pamw.15698
|View full text |Cite
|
Sign up to set email alerts
|

Still diagnosed too late and under-recognized? A first comprehensive report on primary hyperoxaluria from Poland

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution-NonCommercial-ShareAlike 4.0 International License (CC BY-NC-SA 4.0), allowing third parties to copy and redistribute the material in any medium or format and to remix, transform, and build upon the material, provided the original work is properly cited, distributed under the same license, and used for noncommercial purposes only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…In relation to the current Polish population of about 38 million people, this number suggests a much lower cystinosis incidence in Poland than in Western countries. Interestingly, the similar epidemiological discrepancy we have recently found in relation to primary hyperoxaluria-the other, very rare monogenic disorder leading to ESKD [25].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In relation to the current Polish population of about 38 million people, this number suggests a much lower cystinosis incidence in Poland than in Western countries. Interestingly, the similar epidemiological discrepancy we have recently found in relation to primary hyperoxaluria-the other, very rare monogenic disorder leading to ESKD [25].…”
Section: Discussionsupporting
confidence: 82%
“…). rhGH was not used in patients 12.1 and 12.2, however they showed a normal growth at25-50 and 10-25 percentiles at the current age of 13 and 11 years, respectively. Overall 3/13 INC patients died during the follow up.…”
mentioning
confidence: 99%
“…The next most common variants were c.569C>T (AF, 8%) and c.944-46delAGG (AF, 5.3%). Eleven novel pathogenic variants were identified (Table 2 5,6,[9][10][11][20][21][22][23][24][25][26][27][28][29] ).…”
Section: Diagnosismentioning
confidence: 99%
“…To date, most genotypes identified in PH3 patients have not been associated with severe phenotypes. Sikora et al [35] found that all patients with c.700+5G>T retained normal renal function, and only one-third of these patients showed recurrent urolithiasis. Other common mutations (c.860G>T, c.944_946delAGG, and c.907C>T) in HOGA1 are also considered associated with milder phenotypes [36,37].…”
Section: Human Mutationmentioning
confidence: 99%